DESIGN OF COASTAL PROTECTION STRUCTURE AT PENYAK BEACH KABUPATEN BANGKA TENGAH KEPULAUAN BANGKA BELITUNG - Rifqi, Trisnaldi
Indonesia is one of the maritime countries that has a coastline of 99,093 kilometers. Some of them are used as places of recreation or tourism, for example Penyak Beach in Central Bangka Regency, Bangka Belitung Islands. However, the development of increasingly advanced facilities and infrastructure has caused the coastline on Pantai Penyak to experience a significant setback from year to year. The coastline which is increasingly retreating if left unchecked will certainly have an impact on the lives of local people and visiting tourists. Therefore, to overcome this problem, it is necessary to plan for the construction of a coastline on Penyak Beach, which is right at the points where the coastline changes have a major impact. The coastline decline caused by natural factors or human activities was analyzed using the Generalized Model for Simulating Shoreline Change (GENESIS) Coastal Engineering Design and Analysis System (CEDAS) program. GENESIS will simulate shoreline retreats and implement appropriate coastal safeguards to overcome this setback. The coastal safety structures that are modeled are Groin, Breakwater, Revetment, and combination / combination of these buildings. The result was found that the appropriate beach protection building was a breakwater. The selected breakwater or breakwater building is 13 pieces with a length of 100 m each and placed at a distance of 55 meters from the coastline, and the distance between the breakwaters is 30 meters. The breakwater structure consists of armor layers made of tetrapod, filter layers and cores composed of natural stones of different sizes, and toe protection layers.